Evaluating Radiation Exposure to Oral Tissues in C-Arm Fluoroscopy A Dose Analysis - YAZICI, Selma Dilara; GÜNAY, Osman; TUNÇMAN, Duygu; KESMEZACAR, Fahrettin Fatih; YEYİN, Nami and AKSOY, S. Hilmi and DEMIR, Mustafa and ÇAVDAR KARAÇAM, Songül (International Journal of Computational and Experimental Science and Engineering, 2024)
This study investigates the radiation dose to oral mucosal tissues during C-arm fluoroscopy imaging using an Alderson Rando phantom and thermoluminescent dosimeters (TLD-100) for precise measurements. The aim is to assess the potential risks for patients and healthcare personnel exposed to ionising radiation during these procedures. The Alderson Rando phantom, a human-equivalent model, was utilized to simulate radiation exposure in a controlled environment. TLD-100 dosimeters were strategically positioned in the 6th section of the phantom and exposed to radiation at intervals of 0.5, 1, 2, 4, and 8 minutes. The experiments were carried out at Hisar Hospital Intercontinental and the dosimeter readings were then evaluated at Çekmece Nuclear Research Centre. The study demonstrated that the mean radiation doses affecting the internal tissue of the oral mucosa were 0.912 mSv (0.5 minutes), 1.604 mSv (1 minute), 2.719 mSv (2 minutes), 6.763 mSv (4 minutes), and 13.811 mSv (8 minutes). The mean radiation doses affecting the lip skin tissue were 1.423 mSv (0.5 minutes), 2.435 mSv (1 minute), 5.2 mSv (2 minutes), 10.195 mSv (4 minutes), and 17.404 mSv (8 minutes). Results indicate a direct relationship between radiation dose and exposure time, with increasing doses observed at longer exposure times. This research aims to improve patient safety during C-arm scope imaging procedures by determining precise radiation dosage levels for oral mucosal tissues and addressing the lack of published reference values in the literature.